2023
DOI: 10.1029/2023ja031946
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Birkeland Currents Are More Likely During Geomagnetic Storms on the Dayside of the Earth

John C. Coxon,
Gareth Chisham,
Mervyn P. Freeman
et al.

Abstract: We examine the statistical distribution of large‐scale Birkeland currents measured by the Active Magnetosphere and Planetary Electrodynamics Response Experiment in four unique categories of geomagnetic activity for the first time: quiet times, storm times, quiet‐time substorms, and storm‐time substorms. A novel method is employed to sort data into one of these four categories, and the categorizations are provided for future research. The mean current density is largest during substorms and its standard deviati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 115 publications
(231 reference statements)
0
1
0
Order By: Relevance
“…The spatial variation of the PDF shape and scale was shown to be ordered by the large-scale flow vorticity and the magnetic field-aligned current (FAC) systems that couple the magnetosphere to the high-latitude ionosphere (FAC is proportional to vorticity in the limit of uniform ionospheric conductance). Coxon et al (2022Coxon et al ( , 2023 have shown that PDFs of FACs measured in the ionosphere are similarly leptokurtic, with a similar spatial variation in distribution shape and scale to the flow vorticity.…”
Section: Introductionmentioning
confidence: 94%
“…The spatial variation of the PDF shape and scale was shown to be ordered by the large-scale flow vorticity and the magnetic field-aligned current (FAC) systems that couple the magnetosphere to the high-latitude ionosphere (FAC is proportional to vorticity in the limit of uniform ionospheric conductance). Coxon et al (2022Coxon et al ( , 2023 have shown that PDFs of FACs measured in the ionosphere are similarly leptokurtic, with a similar spatial variation in distribution shape and scale to the flow vorticity.…”
Section: Introductionmentioning
confidence: 94%